BANDWIGTH COMPUTER NETWORKS UNDER AMPLITUDE-FREQUENCY SAMPLING - Василенко, В.; Василенко, М.; Чунарьов, А. (Science-based technologies, 2011)
The questions increase bandwidth computer networks in the use of amplitude-frequency sampling and its coor-dination with the output source.